Design of Distribution Optimization Application using Firefly Algorithm - Ngarap Imanuel Manik; Yunggih Nursalim; Derwin Suhartono (Bina Nusantara University, 2017)
The goal of this research was to optimize the distribution of goods and computerize. The method consisted of problem identification, analysis, implementation, and evaluation. Firefly algorithm was used as a method for optimizing the distribution of goods. The results achieved are the shortest distribution route of goods in accordance with the existing constraints and low cost of distribution. It can be concluded that the research can beused too ptimizethe distribution of goods and tominimize distributioncost.